PSYCHOLOGICAL FEATURES OF THE FORMATION OF MODERN TEACHER-STUDENT RELATIONSHIPS IN FOREIGN EDUCATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article studies the psychological characteristics of the formation of modern teacher-student relationships in foreign education. Based on the results of the research and analysis, proposals and recommendations for the development of psychological aspects of the formation of teacher-student relationships have been developed. Today, in the interaction of a modern school teacher with his students, there is a need to clarify the essence of their methodological foundations and clarify the psychological aspects of the problem. Therefore, according to the data obtained from the results of analytical materials in this area, human interests dominate in a complex way at the heart of the interaction of teachers and students. In particular, it is reflected in the system of interpersonal relationships and the individual's activity, the embodiment of professional skills.